MERCURY TOXICITY IN TWO INTERTIDAL TROPICAL MARINE MOLLUSCS - EKANATH, A E; MENON, N R (Fishery Technology, 2017)
Lethal and sub-lethal effects of mercury have been studied in Perna viridis andModiolus carvalhoi. For P. viridis LC30 is 1.0 p.p.m. at 48 hand 0.23 p.p.m. at 96 h. Recorded LC50 values forM. carvalhoi are 0.5 p.p.m. and 0.19 p.p.m. at 48 hand 96 h respectively. The results document that these two species, although inhabiting the same area in the tidal belt, exhibit clear differences in mercury resistance. It is further shown that the duration of exposure affects mortality rates. In sub-lethal concentration, between 0.01 and 0.10 p.p.m. decrease in pedal-gland activity is conspicuous in P. viridis. At concentrations•much below LC50 values (at 96 h), although some animals are alive, pedal-gland activity is totally suspended, supporting the assumption that shellclosure ability plays a minor role in byssus thread production. In M. carvalhoi total cessation of p~dal gland activity occurred at 0.09 p.p.m. of mercury.